A Modified Hybrid Partitioned VM-Method for Unconstrained Optimization - Abbas Y. AL-Bayati; Basim A. Hassan (Kirkuk Journal of Science, 2012)
In this paper, we have proposed a modified hybrid partitioned VM-method for minimizing a smooth partially separable nonlinear functions. Numerical results indicate that the proposed (modified hybrid) method with it's two different versions was efficient than the standard BFGS formula of VM-method.